Pengelolaan Manajemen Keuangan Keluarga bagi Fiskawati pada Kantor Pelayanan Pajak Kota Pekanbaru - Ng, Martha; Chandra, Jennifer; Wijaya, Evelyn; David, David; Chandra, Teddy; Fransisca, Luciana (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
Managing family finansial is not simple, as it requires planning, financial allocation, implementation and evaluation so that financial management can run effectively and efficiently. This community service activity aims to improve household financial understanding and skill by providing practical knowledge on how to manage finance well. The training was conducted at the Pekanbaru City Tax Service Officer for fiskawati officers to improve understanding of financial concepts and prevent poor financial management. The positive respond demonstrated the relevance and needed for this training, which is expected to improve family financial literacy and well being.